(3GdeMGSHI GdOhdjI hGfYcGSGJgG Ydi GdOhd GdYQHjI (B/s - (3CHh RjO, eMeO GdeHQhcs ((3GdbGgQI(B: s (3GjJQGc ddfTQ hGdJhRjY(B, s, 2005)
(3ebOeI YGeI ddeMGSHI GdOhdjI(B- (3deMI JGQjNjI Yf JWhQ GdeMGSHI(B- (3GdJfXje GdeMGSHj(B- (3GdJfXje GdeMGSHj aj cd ef HQjWGfjG haQfSG(B- (3GdeMGSHI aj GdOhd GdfGejI(B- (3GdYhGed GdHjFjI hYdGbJgG HGdeMGSHI(B- (3GdKbGaI hYdGbJgG HGdeMGSHI(B- (3HYV GdYhGed GdHjFjI GdCNQi GdeDKQI Ydi JWhQ GdfXGe GdeMGSHj(B- (3GdYhGed GdHjFjI hGdJUfja GdeMGSHj(B- (3GdJhGab GdOhdj ddeMGSHI(B- (3GdeMGSHI HGdOhd GdYQHjI(B- (3fXGe GdeMGSHI GdehMOI heOi edGAeJg ddOhd GdYQHjI(B- (3YhGed CNQi JOYe edGFeI GdfXGe GdeMGSHj GdehMO ddHjFI GdYQHjI(B- (3GdeMGSHI aj Xd JZjQ GdCSYGQ hGdJVNe(B- (3CSYGQ GdJMhjd(B- (3JQLeI GdYedjGJ hGdbhGFe GdeGdjI GdCLfHjI(B- (3GdEaUGM GdeMGSHjs
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdOhdjIs; (3GdeMGSHI(B- (3GdOhd GdYQHjIs